Temperamental and anti-social factors affecting how primary school children make and keep friends - Teoh, Hsien-Jin * (Sunway University College, 2006)
In this study, 398 primary school children were investigated to ascertain how aggressive behaviours and selfreported temperamental traits affect children?s social support from their friends. The results indicate that changes in aggressiveness and the child?s mood and flexibility predicted social support from classmates. More specifically, anti-social behaviours such as jealousy and showing off, and poor interpersonal behaviours such as not smiling and being inflexible resulted in lower levels of classmate support.